Intravenous Immunoglobulin Therapy Restores the Quantity and Phenotype of Circulating Dendritic Cells and CD4+ T Cells in Children With Acute Kawasaki Disease - Wang, Nana; Chen, Zhongyue; Zhang, Fan; Zhang, Qianwen; Sun, Ling; Lv, Haitao; Wang, Bo; Shen, Jie; Zhou, Xufang; Chen, Feiyan; Zhang, Binwei; Meng, Lijun; et al. (Frontiers in Immunology, 2022)
Background Intravenous immunoglobulin (IVIG) showed its therapeutic efficacy on Kawasaki disease (KD). However, the mechanisms by which it reduces systemic inflammation are not completely understood. Dendritic cells (DCs) and T cells play critical roles in the pathogenic processes of immune disorders. Assessing the quantity of DC subsets and T cells and identifying functional molecules present on these cells, which provide information about KD, in the peripheral blood may provide new insights into the mechanisms of immunoglobulin therapy. Methods In total, 54 patients with KD and 27 age-matched healthy controls (HCs) were included in this study. The number, percentage, and phenotype of DC subsets and CD4+ T cells in peripheral blood were analyzed through flow cytometry. Results Patients with KD exhibited fewer peripheral DC subsets and CD4+ T cells than HCs. Human leucocyte antigen-DR (HLA-DR) expression was reduced on CD1c+ myeloid DCs (CD1c+ mDCs), whereas that on plasmacytoid DCs (pDCs) did not change significantly. Both pDCs and CD1c+ mDCs displayed significantly reduced expression of co-stimulatory molecules, including CD40, CD86. pDCs and CD1c+ mDCs presented an immature or tolerant phenotype in acute stages of KD. Number of circulating pDC and CD1c+ mDC significantly inversely correlated with plasma interleukin-6 (IL-6) levels in KD patients pre-IVIG treatment. No significant differences were found concerning the DC subsets and CD4+ T cells in patients with KD with and without coronary artery lesions. Importantly, these altered quantity and phenotypes on DC subsets and CD4+ T cells were restored to a great extent post-IVIG treatment. T helper (Th) subsets including Th1 and Th2 among CD4+ T cells did not show alteration pre- and post-IVIG treatment, although the Th1-related cytokine IFN-γ level in plasma increased dramatically in patients with KD pre-IVIG treatment. Conclusions pDCs and CD1c+ mDCs presented an immature or tolerant phenotype in acute stages of KD, IVIG treatment restored the quantity and functional molecules of DCs and CD4+ T cells to distinct levels in vivo, indicating the involvement of DCs and CD4+ T cells in the inflammation in KD. The findings provide insights into the immunomodulatory actions of IVIG in KD.